VOCABULARY LEARNING STRATEGIES USED BY ENGLISH DEPARTMENT STUDENTS - Theresiawati , Septiana; Timotius, Anne Indrayanti (ELTR Journal, 2017)
This research was done on vocabulary learning strategies (VLS) among EnglishDepartment (ED) students. The main purpose of this study was to investigate theVLS that were mostly used by ED students. The two sub-questions were: (1)What are the most frequent VLS used? and (2) What are the most useful VLS forED students? To find the answer, this study used a questionnaire adapted fromSchmitt’ s (2004) VLS taxonomy. After analyzing the questionnaires from 100participants, it was discovered that some of the most preferred and useful VLSwere opening the dictionary and repeating the word in mind frequently.